Culto de Tomé : origem, manifestações, relevância e conseqüências - Reis, Ana Isa dos (2006)
The subject of the dissertation is the phenomenon called the Liturgy of St. Thomas. The first chapter gives information about the origin of the Liturgy of St. Thomas in Finland. Following this, the arrival and the expansion of the Liturgy of St. Thomas in congregations of the Evangelical Church of the Lutheran Confession in Brazil is presented and the present liturgical manifestations of the Liturgy of St. Thomas within the context of the congregations of the Evangelical Church of the Lutheran in Brazil are described. The second chapter examines the relevance of the Liturgy of St. Thomas for those who participate in it. The principal topics which the participants indicated as important are presented. The third chapter interprets the phenomenon, Liturgy of St. Thomas, and finally, extracts consequences that apply to doing liturgy today.